2023
DOI: 10.3389/fmars.2023.1076870
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to polychlorinated biphenyls (PCBs) affects the histology and antioxidant capability of the clam Cyclina sinensis

Abstract: Polychlorinated biphenyls (PCBs) are environmentally persistent and highly toxic organochlorine compounds that may cause toxic effects on aquatic animals. In this study we assess the toxic effect of PCBs on a bivalve used in aquaculture, the clam Cyclina sinensis. To this end, individuals of C. sinensis were exposed for 72 h at two PCB concentrations (1 ng/L and 10 ng/L) and control (absence of PCBs). At the end of the exposure, the hemolymph, hepatopancreas, and gills samples of C. sinensis were harvested for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Symptoms reported in the workplace include slight irritation to skin and eyes at airborne levels above 0.1 mg per cubic meter with intolerable irritation occurring above 10 mg per cubic meter (3). In a comparison study in animals, (13) showed that acute PCB exposure decreased the survival rate of Cyclina sinensis mussels compared to controls. Acute PCB exposure regulates the enzymatic activities of superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-Px) and malondialdehyde (MDA) content in C. sinensis hemolymph, while decreasing nonspecific enzymatic regulation of alkaline phosphatase (AKP).…”
Section: Acute Toxicitymentioning
confidence: 99%
“…Symptoms reported in the workplace include slight irritation to skin and eyes at airborne levels above 0.1 mg per cubic meter with intolerable irritation occurring above 10 mg per cubic meter (3). In a comparison study in animals, (13) showed that acute PCB exposure decreased the survival rate of Cyclina sinensis mussels compared to controls. Acute PCB exposure regulates the enzymatic activities of superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-Px) and malondialdehyde (MDA) content in C. sinensis hemolymph, while decreasing nonspecific enzymatic regulation of alkaline phosphatase (AKP).…”
Section: Acute Toxicitymentioning
confidence: 99%
“…Contaminant accumulation has been reported in crustacean hepatopancreas [334][335][336] and in the skin, viscera, bones, and scales of fish [337][338][339][340][341]. Mollusks also accumulate toxicants [342][343][344][345], with the digestive glands and gills of hard-shelled animals representing preferential accumulation sites [346][347][348]. The presence of marine biotoxins may represent a very concrete challenge for the use of marine animal co-products.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%